Perempuan dan Pembangunan Sektor Pertanian - Tutuk Ari Arsanti (Jurnal Maksipreneur, 2013)
The importance of prividing capacity women farmer in the agricultural sector bring a great impact on the development of the Indonesia’s agricultural sector. This articles written to give a description of how the role of women in the development of the agricultural sector. A qualitative approach trough a method of participation action reseacrh used to obtain the image and problem solving faced. It will provide understanding in more well of potential for development agriculture in various line including potential for development entrepreneurship based agriculture by women. This research result indicates that the woman’s role in efforts to improve the development of the agricultural sector through the development of entrepreneurial-based agriculture is very high. The importance of increasing the capacity of peasant women in the agricultural sector to be very needed in order to the development of agriculture especially for smal-medium scale of farming.